Ibuprofen and COVID-19 disease: separating the myths from facts. (3rd August 2021) - Poutoglidou, Frideriki; Saitis, Athanasios; Kouvelas, Dimitrios
ABSTRACT: Introduction : The Coronavirus disease 2019 (COVID-19) poses novel challenges in the healthcare systems around the world. Concern about the role of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and, in particular, ibuprofen has led to significant speculation. Areas covered : A literature search was conducted to evaluate ibuprofen's potential benefits and harms in the COVID-19 disease. Angiotensin-Converting Enzyme 2 (ACE-2) is crucial entry receptor for Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2) in host cells. We found no scientific evidence linking ibuprofen use and an ACE-2 overexpression. Ibuprofen suppresses the production of various pro-inflammatory cytokines that are implicated in the 'cytokine storm' and subsequent ARDS in COVID-19 disease. Nevertheless, the exact role of ibuprofen in the immune response in COVID-19 disease is still unknown. There are no double-blind, placebo-controlled studies assessing the effect of ibuprofen on COVID-19 disease progression. Expert opinion : The studies that have been performed so far demonstrate no association between ibuprofen use and increased mortality rates or an increased risk for respiratory support. Accordingly, we recommend ibuprofen to be used for managing COVID-19 symptoms.